Personality Traits and Entrepreneurial Intention: A Study of Business Student Perspectives - Puskar Prasad Pokharel (Pravaha, 2023)
This study examines the key personality trait factors such as Need for Achievement, Innovativeness, Risk Tolerance and Self-efficacy have an influence on Entrepreneurial Intention among Management Students with moderating effect of entrepreneurship education. Data were collected from 410 MBS students of constituent colleges of TU; 4th semester students (with entrepreneurship course) and 1st semester students (without entrepreneurship course). The obtained data were analyzed using One-way ANOVA, Correlation Coefficient and Multiple Regression Analysis. The study revealed that the Need for Achievement and Self-efficacy has a significant positive relationship with entrepreneurial intention. Among the four personality trait factors (Need for Achievement, Innovativeness, Risk Tolerance and Self-efficacy), the study revealed that students risk taking propensity interacts with education. Therefore, the study depicted that entrepreneurship education does not have a positive moderating effect on other personality trait factors except risk tolerance. Similarly, the One-way ANOVA results depicted that gender, age group, colleges, entrepreneurship education (Semester) and Parent’s Profession has no statistically significant difference in terms of entrepreneurial intention. These findings suggest that MBS students of constituent colleges of TU have shown only two personality traits factors (need for achievement and self- efficacy) that have influence on entrepreneurial intention. The results of the study may have insightful implications for researchers, university educators and policy makers.